Impact of natural disasters on student enrollment in higher education programs: A systematic review - Jing Wang (Heliyon, 2024)
This study aims to evaluate how natural disasters affect student enrollment in higher education programs, considering both immediate and long-term consequences. The PRISMA guidelines were adhered to in conducting this review. Multiple databases, such as Web of Science and Scopus, including those with articles from January 2000 to February 2023, were thoroughly searched. Articles focusing on how natural disasters affect students' enrollment in higher education programs met the inclusion requirements. A total of 22 studies were deemed eligible for inclusion and detailed analysis. The findings suggest that natural disasters have a negative influence on higher education enrollment, with the most severe effects being felt by disadvantaged populations. This study reveals that natural disasters impact various aspects of the enrollment process, such as application, acceptance, registration, attendance, retention, and graduation, in higher education due to infrastructural and psychological impacts. Key variables linking natural disasters to enrollment changes include damage to institutional infrastructure, economic and psychological strain, resource limitations, loss of social support networks, and disruptions to academic programs. Enhancing resilience involves adopting online learning, providing financial support, flexible enrollment policies, mental health services, disaster preparedness training, resilient infrastructure development, and collaborative institutional programs. The study highlights the need for comprehensive, context-specific disaster management strategies that address both immediate and long-term educational needs. It identifies potential solutions, including online learning platforms, financial aid, flexible enrollment policies, mental health support, disaster preparedness training, infrastructure resilience, and collaborative programs with other institutions. Context-specific programs are essential to support impacted students by rebuilding educational infrastructure and providing financial and emotional support, thereby ensuring their continued access to higher education. This study offers valuable insights for disaster management, educational policy, and future research on this critical issue.